FAKTOR-FAKTOR PENTING YANG MEMENGARUHI ANTUSIAS JEMAAT DALAM BERIBADAH - Kahar Umbu Djawaray; David Chandra Kirana (STT Kristus Alfa Omega, 2021)
Based on the temporary observations, the researcher found that the congregation at the Beth-El Tabernacle Church Shekinah Glory Semarang was less enthusiastic about worshiping. This study aims to find out how good the values of the factors that influence the enthusiasm of the congregation in worshiping and to find out what is the most dominant factor. The method used is descriptive quantitative method, and it turns out that the value is very high or 90.6% and the most dominant factor is the factor of the Holy Spirit's work with a value of 95% or very high interpretation.